2021
DOI: 10.26753/empati.v2i2.630
|View full text |Cite
|
Sign up to set email alerts
|

Pelatihan Spiritual Emotional Freedom Technique (Seft) Untuk Meningkatkan Kualitas Tidur Dan Stabilitas Tekanan Darah Pasien Hipertensi

Abstract: Tekanan darah yang tidak stabil pada penderita hipertensi dapat diakibatkan oleh kebutuhan istirahat tidur tidak terpenuhi. Kualitas tidur yang kurang disertai tekanan darah tinggi yang tidak tertangani dengan baik akan berdampak pada munculnya komplikasi dan resiko terburuk terjadi kematian. Upaya mengendalikan hipertensi dapat dilakukan dengan terapi komplementer Spiritual Emotional Freedom Technique (SEFT). Tujuan dilakukannya pengabdian masyarakat ini adalah meningkatkan pengetahuan dan kemampuan penderita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 8 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…A study by Sartika and Suprayitno (2018) on 30 participants divided into two groups-15 participants as the intervention group and 15 participants as the control group-found that 10 participants had a low level of education (66.7%), which may have an impact on their level of knowledge about health and awareness of the value of health for oneself. The study, which involved 44 respondents from prolanis-using hypertension patients, found that 14.8% of the respondents had low levels of education, and it concluded that the level of education can affect how well the mas community understands the value of SEFT non-pharmacological therapy for improving sleep quality and blood pressure stability in hypertensive patients (Kristinawati et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…A study by Sartika and Suprayitno (2018) on 30 participants divided into two groups-15 participants as the intervention group and 15 participants as the control group-found that 10 participants had a low level of education (66.7%), which may have an impact on their level of knowledge about health and awareness of the value of health for oneself. The study, which involved 44 respondents from prolanis-using hypertension patients, found that 14.8% of the respondents had low levels of education, and it concluded that the level of education can affect how well the mas community understands the value of SEFT non-pharmacological therapy for improving sleep quality and blood pressure stability in hypertensive patients (Kristinawati et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…This situation causes the fishermen's rest time to decrease. Lack of rest can cause systolic and diastolic blood pressure to increase (Kristinawati et al, 2021).…”
Section: Health Maintenance Behavior Of Hypertension Sufferersmentioning
confidence: 99%
“…Other researchers suggest that poor health behavior is drinking alcohol compared to those who do not drink alcohol with scores p-value (0,000), So alcohol is a risk factor for hypertension (Zhao et al, 2020). Lack of adequate rest can affect the occurrence of rising blood pressure (Kristinawati et al, 2021).…”
Section: Introductionmentioning
confidence: 99%